Digital Journalism and News and Feature Video Writing in the 21st Century - Yamthap, Sunanta; Siriphon, Aranya (Journal of Business, Innovation and Sustainability (JBIS), 2022)
With the advent of the digital era in the 21st century, the process of news writing and news documentary production has changed significantly. The new media context has made traditional news writing and news documentary production less relevant. This article examined the refreshed knowledge about news writing and news documentary production, to be adapted for the context of Thailand. The document research suggested that a novel news writing and news documentary production style is needed to satisfy news consumers and internet users, and especially to meet the unique characteristic of open and informative online media. Current information technologies have allowed newsrooms and journalists to apply dimensions of speed, depth, and user control to the new news writing style. In addition, journalists should learn how to produce and tell stories through news documentaries and feature videos, to improve their multitasking skills which have become extensively necessary against the backdrop of multimedia journalism in the digital age.